2016
DOI: 10.1177/1049909116659737
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in Undergraduate Medical Education—How Far Have We Come?

Abstract: There is significant progress in palliative care education within medical schools. Ongoing challenges relate to correlating our current practice in medical education to professional recommendations and the expressed needs of junior doctors to practice competent end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 113 publications
0
34
0
5
Order By: Relevance
“…Another point of attention is the content of PC education programs. Findings from an international review show that concepts of pain management are being well addressed, but current undergraduate curricula may not adequately explore issues of broader symptom control, and psychosocial and spiritual aspects of care ( 28 ). The need and wish for these educational initiatives is also mentioned by Chang et al ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another point of attention is the content of PC education programs. Findings from an international review show that concepts of pain management are being well addressed, but current undergraduate curricula may not adequately explore issues of broader symptom control, and psychosocial and spiritual aspects of care ( 28 ). The need and wish for these educational initiatives is also mentioned by Chang et al ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients die because of chronic ailments; however, students left without proper guidance and knowledge regarding palliative care. Palliative care is the only method that improves the quality of life and provides a solution for numerous problems related to life-threatening illness for the patients and their family members (Fitzpatrick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several students, residents and trained doctors reported that they did not receive formal training in PC during their undergraduate and medical residency and do not feel quali ed to attend terminally ill patients [6,7]. In 2013, the Education Group of European Association for Palliative Care de ned ten core competencies in PC [8,9] PC are a part of medical education and it would be appropriate to identify which competencies were acquired and which could be improved during medical undergraduation.…”
Section: Introductionmentioning
confidence: 99%